Heart rate variability – clinical significance - Urbanik, Dominika; Podgórski, Maciej; Mazur, Grzegorz (Family Medicine & Primary Care Review, 2018)
Heart rate variability (HRV) is a statistical evaluation of ECG Holter analysis used for non-invasive assessment of autonomic nervous system activity. The autonomic nervous system plays a major role in human homeostasis. Autonomic dysfunction and altered HRV are observed in many life-threatening conditions, like myocardial infarction, multiple organ dysfunction syndrome, sepsis and severe brain injuries. Analysis of HRV uses two major techniques for assessing ECG intervals – time and frequency analysis. Additionally, there is also an alternative non-linear method of assessing HRV called fractal analysis. Clinical evaluation of HRV has been performed in medicine for more than three decades. Recent studies show that heart rate variability is a strong predictor of cardiovascular risk and mortality. It has also become common practice in everyday medicine, especially in family medicine, cardiology, neurology and psychiatry. There are some variables affecting HRV analysis: age, gender, physical activity and body mass index. Age and body mass index have negative correlation with HRV. Correlation of gender with HRV is not clearly specified in literature. Recent studies show that young males have increased HRV, and this diminishes faster during aging. Young women present decreased values of HRV, but these differences become indistinguishable after 50. Physical activity may enhance HRV by increasing vagal tone and decreasing sympathetic activity.